Five‐year follow‐up of intracoronary autologous cell therapy in acute myocardial infarction: the REGENERATE‐AMI trial. (18th January 2022) - Mathur, Anthony; Sim, Doo Sun; Choudry, Fizzah; Veerapen, Jessry; Colicchia, Martina; Turlejski, Tymoteusz; Hussain, Mohsin; Hamshere, Stephen; Locca, Didier; Rakhit, Roby; Crake, Tom; Kastrup, Jens; et al.
Abstract: Aims: The long‐term outcomes of the intracoronary delivery of autologous bone marrow‐derived cells (BMCs) after acute myocardial infarction are not well established. Following the promising 1 year results of the REGENERATE‐AMI trial (despite it not achieving its primary endpoint), this paper presents the analysis of the 5 year clinical outcomes of these acute myocardial infarction patients who were treated with an early intracoronary autologous BMC infusion or placebo. Methods and results: A 5 year follow‐up of major adverse cardiac events (defined as the composite of all‐cause death, recurrent myocardial infarction, and all coronary revascularization) and of rehospitalization for heart failure was completed in 85 patients (BMC n  = 46 and placebo n  = 39). The incidence of major adverse cardiac events was similar between the BMC‐treated patients and the placebo group (26.1% vs. 18.0%, P  = 0.41). There were no cases of cardiac death in either group, but an increase in non‐cardiac death was seen in the BMC group (6.5% vs. 0%, P  = 0.11). The rates of recurrent myocardial infarction and repeat revascularization were similar between the two groups. There were no cases of rehospitalization for heart failure in either group. Conclusion: This 5 year follow‐up analysis of the REGENERATE‐AMI trial did not show an improvement in clinical outcomes for patients treated with cell therapy. This contrasts with the 1 year results which showed improvements in the surrogate outcome measures of ejection fraction and myocardial salvage index.